Financial Ratios of Companies Before and After Initial Public Offering (IPO) - William Tjong; Kevin Fedora (Universitas Pelita Harapan, 2024)
This study aims to examine differences in the company's financial ratios before and after the Initial Public Offering (IPO) in terms of profitability, solvency, liquidity, activity and growth ratios. This study uses quantitative research by conducting a different test analysis using the Wilcoxon Signed Ranks Test and the ANOVA test on the financial statements of all companies (except finance) that have conducted IPOs for the study period. Based on the test results, it can be seen that the trend of financial performance in terms of profitability, solvency, liquidity, activity and growth ratios shows a decline trend in the ratio of profitability, solvency, liquidity, activity and growth. Based on the results of the different test using the Wilcoxon Signed Ranks Test method, it is shown that the ratios of profitability, solvency, liquidity, activity and growth have differences before and after the IPO. Based on the ANOVA test to analyze the average change in the sample, it is known that the ROE ratio changes in the sample average, while the DER, CR, Asset Turnover and Sales Growth ratios do not change in the sample average.